The Relevance of Emotions in Presidential Public Appeals: Anger's Conditional Effect on Perceived Risk and Support for Military Interventions. - Villalobos, José D.; Sirin, Cigdem V. (Presidential Studies Quarterly, 2017)
This study investigates whether and to what extent the thematic relevance of emotive stimuli embedded in presidential speeches affects people's risk perceptions and policy support regarding military interventions in civil conflict. Conducting an experimental study with a total of 1,187 participants, we find the induction of anger via thematically relevant emotive triggers leads to higher levels of support for military interventions in civil conflict even though people's risk perceptions-which were high across all conditions-remain unaffected. By comparison, the effects of anger on policy support observed in the thematically irrelevant condition do not differ significantly from the emotion-neutral control condition. Thus, although members of the public are highly sensitive to the risks of military interventions in civil conflict and can compartmentalize their feelings within the relevant policy sphere (thereby negating a spillover effect), stimulated anger can nevertheless generate greater public support for military interventions. Still, the potential for such opinion movement to help justify and facilitate policy action depends highly on the president's strategic positioning.